Human T-Cell Leukemia Virus Type I-Mediated Repression of PDZ-LIM Domain-Containing Protein 2 Involves DNA Methylation But Independent of the Viral Oncoprotein Tax - Pengrong Yan; Zhaoxia Qu; Chie Ishikawa; Naoki Mori; Gutian Xiao (Neoplasia: An International Journal for Oncology Research, 2009)
Human T-cell leukemia virus type I (HTLV-I) is the etiological agent of adult T-cell leukemia (ATL). Our recent studies have shown that one important mechanism of HTLV-I-Mediated tumorigenesis is through PDZ-LIM domain-containing protein 2 (PDLIM2) repression, although the involved mechanism remains unknown. Here, we further report that HTLV-I-Mediated PDLIM2 repression was a pathophysiological event and the PDLIM2 repression involved DNA methylation. Whereas DNA methyltransferases 1 and 3b but not 3a were upregulated in HTLV-I-transformed T cells, the hypomethylating agent 5-aza-2′-deoxycytidine (5-aza-dC) restored PDLIM2 expression and induced death of these malignant cells. Notably, the PDLIM2 repression was independent of the viral regulatory protein Tax because neither short-term induction nor long-term stable expression of Tax could downregulate PDLIM2 expression. These studies provide important insights into PDLIM2 regulation, HTLV-I leukemogenicity, long latency, and cancer health disparities. Given the efficient antitumor activity with no obvious toxicity of 5-aza-dC, these studies also suggest potential therapeutic strategies for ATL.